2005
DOI: 10.1111/j.1365-2842.2005.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of two distal extension removable partial denture designs on tooth stabilization and periodontal health

Abstract: A 30-month follow-up study was conducted on 36 patients to evaluate the effects of the lingual plate as a major connector in distally extended removable partial dentures (RPDs) on tooth stabilization. At the same time, the study evaluated the effects of lingual plate-type RPDs and lingual bar-type RPDs on periodontal health. The most striking finding of the study was that, with the exception of gingival recession (GR), periodontal conditions improved with both types of RPDs. At the end of 30 months, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 41 publications
2
48
0
6
Order By: Relevance
“…La eventual excesiva rigidez de este complejo retentivo, debe a nuestro entender soslayarse, puesto que se est谩 en presencia de un caso "l铆mite" en cuanto a los recursos de que disponemos para que la pr贸tesis tenga una m铆nima retenci贸n funcional y adem谩s, porque sabemos emp铆ricamente que la mayor o m谩s relevante agresi贸n que puede resultar biomecanicamente perjudicial para un diente, proviene de la periodontitis y su potencial resultado de reabsorci贸n 贸sea alveolar (14,15) . Tambi茅n hemos generado otra modificaci贸n, eliminando la plataforma disto proximal del dise帽o original.…”
Section: Discussionunclassified
“…La eventual excesiva rigidez de este complejo retentivo, debe a nuestro entender soslayarse, puesto que se est谩 en presencia de un caso "l铆mite" en cuanto a los recursos de que disponemos para que la pr贸tesis tenga una m铆nima retenci贸n funcional y adem谩s, porque sabemos emp铆ricamente que la mayor o m谩s relevante agresi贸n que puede resultar biomecanicamente perjudicial para un diente, proviene de la periodontitis y su potencial resultado de reabsorci贸n 贸sea alveolar (14,15) . Tambi茅n hemos generado otra modificaci贸n, eliminando la plataforma disto proximal del dise帽o original.…”
Section: Discussionunclassified
“…Periodic checkup and oral hygiene measures of RPDs' users are essential to improve periodontal health and prosthesis longevity [17]. In contrary, Cosme et al, reported that there is no relation between oral hygiene and prosthesis [5,18].…”
Section: Hygienementioning
confidence: 99%
“…In a study done by Janaina et al, it was concluded that RPDs en-OPEN ACCESS http://scidoc.org/IJDOS.php hanced tooth mobility, diminished prevalence of caries and did not induce the fractures of abutments [62]. For RPDs longevity and improve periodontal health in RPDs' users, satisfactory and regular oral hygiene conditions checkups were required [17].…”
Section: Gingival and Periodontal Conditionsmentioning
confidence: 99%
“…1 Penelitian klinis menunjukkan bahwa penyembuhan setelah perawatan penyakit periodontal berupa pembentukan dan maturasi jaringan lebih baik pada gigi yang tidak mengalami kegoyangan dibandingkan dengan gigi yang goyang. 2 Gigi goyang cenderung memiliki prognosis yang lebih buruk dan respon yang kurang baik terhadap terapi periodontal. 3 Splinting diharapkan dapat membantu peningkatan perlekatan jaringan periodontal pada kasus-kasus periodontitis.…”
Section: Pendahuluanunclassified